Protective Effect of Nalbuphine Combined With Dexmedetomidine on the Lungs of Children With Atelectasis and Foreign Body in the Bronchus During the Perioperative Period - Wang, Yuan; Han, Hong-Yang; Jia, Ying-Ping; Zhao, Li-Yuan; Li, Ying; Zuo, Bian-Jing; Zhang, Jie (Frontiers in Physiology, 2022)
Objective: The present study aims to explore the protective effect of nalbuphine combined with dexmedetomidine on the lungs of children with atelectasis who have a foreign body in a bronchus during the perioperative period. Methods: A total of 180 patients whose computed tomography scan showed atelectasis and a foreign body in a bronchus were randomly divided into three groups: Group C (conventional anesthesia group), Group D (dexmedetomidine group), and Group N+D (nalbuphine combined with dexmedetomidine group). The following indicators were recorded: (1) heart rate (HR) and mean arterial pressure (MAP) prior to induction (T0), at bronchoscope placement (T1), at intubation after surgery (T2), at tube removal (T3), 10 min after tube removal (T4), 20 min after tube removal (T5), and at awaking (T6); (2) monocyte toll-like receptors (TLRs) TLR⁃2, TLR⁃4, tumor necrosis factor α, interleukin 6, oxygenation index, and the B-line sum at T0, T3, 2 h (T7), and 24 h (T8) after tube removal; and (3) hospital stay after surgery. Results: Compared with Group C, in Group D and Group N+D (1) the HR and MAP at T1~T6 were lower; (2) the inflammatory factor indicator and B-line sum were lower and the oxygenation index was higher at T7 and T8; (3) the agitation and cough scores were decreased during tube removal; and (4) the Ramsay sedation score was higher and ventilator weaning time was shortened at T4~T6 (p < 0.05). Compared with Group D, in Group N+D (1) the inflammatory factor indicator and B-line sum were lower at T8; and (2) the oxygenation index was higher (p < 0.05). Compared with Groups C and D, in Group N+D the length of hospital stay was decreased (p < 0.05). Conclusion: In patients with atelectasis and a foreign body in a bronchus during the perioperative period, nalbuphine combined with dexmedetomidine may be capable of reducing the oxidative stress response, improving the oxygenation index, decreasing the pulmonary fluid content, protecting the lung, and facilitating postoperative recovery.